Elektabilitas Calon Legislatif DPRD Dapil I Provinsi Jawa Tengah Pada Pemilu Legislatif 2014 (Dilihat Dari Perspektif Pandangan Pemilih) - Jendra, Bre Ikra; Utomo, Susilo; S, Rr Hermini (Journal of Politic and Government Studies, 2014)
Electability can be sized for the participants in the legislative election strategy to do to win elections more effectively and efficiently. The current electability becomes the most important factor for political parties and candidates in the competition for seats in parliament. Electability is measured by how much of a political party or candidates chosen by voters, but in determining the choice voters will have their own perception and assessment against a political party or candidate. Political culture , the level of political participation and voting behavior be the determining factor of a political party or candidate shall be elected by the voters or even not selected. So that voters become a major actor in the legislative elections. Purpose of this study was to determine and describe electability political parties and candidates in the Central Java provincial assembly constituency 1 (Unggaran , Kendal , Semarang and Salatiga) for the legislative elections of 2014 (viewed from the perspective of voters view). Sampling method in this study using a multistage random sampling with a sample of 400 respondents consisting of the voters who have registered as voters for the legislative elections of 2014 remain. The analysis technique used in this study is a descriptive analysis , frequencies analysis and crosstab analysis. The result show that the public has an ideal candidate criteria based perspective view of voters and political parties electability is not directly proportional to the electability candidates.